TANGGUNG JAWAB BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA BEKASI DALAM PERTANGGUNG JAWABAN KEUANGAN DAERAH TAHUN 2020 – 2021: Responsibilities of The Regional Financial and Asset Management Agency of Bekasi City in Regional Financial Accountability 2020 – 2021 - Mazya, Khairunnisa; Wiratno (Faculty of Law, Universitas Trisakti, 2024)
There was a jump in the budget allocation sourced from the 2021 Bekasi City APBD based on the 2021 Fiscal Year LKPD issued by the Bekasi City Regional Financial and Asset Management Agency. Encouraging this research to answer problems regarding the authority of the Bekasi City and the responsibilities of the Bekasi City in regional financial accountability for 2020-2021. This research uses a normative method, this method aims to describe the research object, then secondary data is processed qualitatively and conclusions are drawn deductively. Based on this problem, the BPK issued the BPK's LHP, the BPK issued an opinion, namely that originally Reasonable Without Exceptions transitioned to Reasonable With Exceptions. The Corruption Eradication Committee discovered gratification in cases of corruption in goods and services as well as auctions for positions carried out by the Mayor of Bekasi.